Enhanced drug retention by anthracene crosslinked nanocomposites for bimodal imaging-guided phototherapy - Fan, Xiaoshan; Ke, Lingjie; Cheng, Hongwei; Chen, Hu; Li, Zhiguo; Ye, Enyi; Loh, Xian-Jun; Wu, Yun-Long; Liu, Gang; Li, Zibiao (Nanoscale, 2021)
Efficient drug delivery, multifunctional combined therapy and real-time diagnosis are the main hallmarks in the exploitation of precision nanomedicine. Herein, an anthracene-functionalized micelle containing a magnetic resonance imaging (MRI) contrast agent, upconversion nanoparticles (UCNPs) and the photosensitizer IR780 is designed to achieve sustained drug release and enhanced photothermal and photodynamic therapy. The polymer-coated hybrid micelle was achieved by crosslinking anthracene-dimer with UV light ( λ > 300 nm), which is converted from near-infrared (NIR) irradiation upon UCNPs. Besides, the water-insoluble photosensitizer IR780 is introduced into the system to achieve efficient drug delivery and photothermal and photodynamic synergistic therapy. As a consequence of NIR-induced anthracene-dimer formation, the cross-linked nanocomposite shows sustained drug release, and the enhanced retention effect of IR780 could increase the photothermal conversion efficiency. Importantly, the incorporation of 2,2,6,6-tetramethyl-piperidineoxyl (TEMPO) as a nitroxide MRI contrast agent presents the potential for real-time diagnosis via nanotheranostics, and the fluorescence imaging of IR780 is applied to monitor drug distribution and metabolism. This strategy of sustained drug delivery by anthracene-dimer formation through the better penetration depth of NIR-II fluorescence provides an executable platform to achieve enhanced phototherapy in biomedical applications. Core-shell structures of anthracene crosslinked nanocomposites containing upconverting nanoparticles and IR780 are manufactured to achieve better phototherapeutic tumor treatment with MRI/PA bimodal imaging guidance.